Overview Of The Level Of Knowledge About Anemia Among Pregnant Women In The Coastal Area Of Bengkulu City - Jeaneri Mandasyary; Linda Yusanti; Yetti Purnama; Asmariyah Asmariyah; Linda Yulyani (CV. AFDIFAL MAJU BERKAH, 2026)
Anemia among pregnant women remains a significant health problem that can increase the risk of complications for both the mother and the fetus. One of the factors influencing the occurrence of anemia is the level of knowledge possessed by pregnant women. This study aimed to describe the level of knowledge about anemia among pregnant women in the coastal area of Bengkulu City. This research employed a quantitative descriptive design with a cross-sectional approach. The population consisted of all pregnant women in the first, second, and third trimesters who were registered in the working areas of Kandang Health Center, Padang Serai Health Center, and Pasar Ikan Health Center, totaling 738 individuals. A sample of 89 respondents was selected using purposive sampling. Data were collected through questionnaires and analyzed using univariate analysis presented in the form of frequency distributions. The results showed that most respondents were aged 20–35 years. The level of knowledge regarding anemia among pregnant women was predominantly in the good category, with 81 respondents (64.8%), followed by the moderate category with 41 respondents (32.8%), and the poor category with 3 respondents (2.4%). In conclusion, the level of knowledge about anemia among pregnant women in the coastal area of Bengkulu City was predominantly categorized as good.